Literarna zgodovina in koncept literarnega polja - Kos, Dejan (Primerjalna književnost, 2009)
At the turn of the millenium, social and cultural changes place literary history in the typical dilemmas of a differentiated and globalized world. The breakdown of certain old traditions and the dynamics of new environments are leading to the expansion of creative approaches. Promising concept also includes the literary system and the literary field, which have been borrowed from sociology. This paper brings these two concepts closer to cultural, media and hermeneutical studies in a systematic manner, and illustrates the applicability of the transformes model through a short description of the literary historical processes taking place in the European cultural space from the Middle Ages to today.
Keywords: history of literature; literarna zgodovina; sociologija literature; literarni sistem; literarno polje; literatura in mediji; literarne konvencije